The Effect of Regular Basketball Education on Children's Some Anthropometric Parametersand Vertical Jump - Alparslan Ünveren; Mihri Karavelioğlu; Şebnem Şarvan Cengiz (Türk Spor ve Egzersiz Dergisi)
This study aims to examine the effect of 12-week regular basic basketball trainings on anthropometric measurements and vertical jump of children aged 8-10. The experimental group of the research consisted of 40 children whose average age was 9.04 ± 0.77 (years) and the control group consisted of 38 children whose average age was 8.97±0.72 (years).Ability selection was made in order to determine these 78 children forming the experimental and control group. Pretest measurements of 40 children in the experimental group were made before basic basketball trainings that would last for 12 weeks and posttest measurements were made after trainings. The same measurements were taken from the other 38 children in the control group, yet any training was not applied to them.Basic basketball education was given in line with complete recovery principle to the experimental group for 12 weeks-three days a week and 90 minutes a day.SPSS 15.00 package program was used in order to evaluate the data obtained from the study and form the tables. Student's t test was used in the comparison of the experimental and control groups. Also, Wilcoxon test was used in the comparison of each group's pretests and posttests. The values of p lt;0.01 and p lt;0.05 were accepted as significance level for all statistical analysis.